Emotional Quotient and Students’ Mathematical Problem-Solving Proficiency: A Meta-Analysis - Malasari, Putri Nur; Awofala, Adeneye O. A. (Universitas Sarjanawiyata Tamansiswa, 2022)
Mathematical problem-solving proficiency is one of the proficiencies that students must have to learn mathematics. The emotional quotient is one of the variables that influence pupils' capacity students mathematical problem-solving proficiency. Many research publications show that emotional quotient is closely related to students' mathematical problem-solving proficiency. This study aims to prove and validate the correlation between emotional quotient and students' Mathematical problem-solving proficiency. The data was obtained from a search on the Google Scholar database from 2013 to 2021. 23 research publications in Indonesia and Nigeria that met the criteria required as samples. Data analysis used a quantitative meta-analysis approach with a correlation meta-analysis. The findings reveal a positive and substantial correlation (5% significance level) between students' emotional quotient and students’ mathematical problem-solving proficiency. The mean effect size is 0.761 (high category) in the range of 0.578 and 0.944. This result demonstrates the coherence of the findings of the examined studies.